Towards quantum optics experiments with trapped atoms in a hollow-core fibre - Jammi, Sindhu (2018)
A proposal for performing quantum memory schemes with a light matter interface in Hollow Core Fibres is introduced. Various technical aspects of implementing such a scheme in the proposed interface are outlined and the different elements required to realize this scheme are discussed, primarily the detection of atomic levels and the extension of the scheme to magnetically trappable levels. A new method to dispersively measure populations and population difference of alkali atoms prepared in their two clock states is introduced, for future use in the Hollow Core Fibre interface. The method essentially detects the atom numbers based on the influence of the linear birefringence in the ensemble on the detection light beams via polarization homodyning. Sideband detection is performed after dressing the atoms with a radio-frequency field to circumvent low-frequency technical noises. The noise performance of this scheme is discussed along with design modifications aimed at reaching the atomic shot noise limit. Another technical aspect of realizing the quantum memory scheme in the proposed light-matter interface is the extension of the scheme to the trappable states of the atomic system as the atoms will be trapped in an atom chip magnetic field. We achieve this extension by showing the microwave spectroscopy of the ground state ensemble of radio-frequency dressed atoms which proves the existence of pseudo one-photon transitions between the trappable clock states. Finally, the preliminary designs and results of integrating an HCF in an atom chip experiment are discussed.